Educating for Peace, the Rule of Law and Development in a new Myanmar - Raynaud, Mael (Journal of Human Rights and Peace Studies, 2016)
Seven years into Myanmar’s political transition, the various political organizations competing for power, along with the public servants, seem to agree in seeing the country as facing three major challenges: bringing about peace, establishing the rule of law, and furthering economic development. Education will be key in training generations of citizens able to deal with these issues and in building a new Myanmar. But State and public institutions remain weak in the new political system established by the 2008 Constitution, described in this article as a hybrid system with elements of democracy and elements of an authoritarian system. In this context, civil society and other providers of education such as monastic schools, private schools, and Ethnic Basic Education Providers (EBEPs), all have a role to play not only as direct providers, but also as partners to the Ministry of Education. White such collaboration already exists, it needs to be strengthened. Yet simply improving the education system will not suffice to achieve the goals professed by the government under the leadership of Daw Aung San Suu Kyi. The social structure of Burmese society, described here as a social Stupa because of its pyramidal shape and notable social, ethnic, gender, and generational inequalities, must be addressed. Generally, a context more conducive to individual freedom, creativity, and critical thinking will be critical to peace, good governance, and economic development.